Four recent books on spirituality and the Psalms: some contextualising, analytical and evaluative remarks - Lombaard, Christo (Verbum et ecclesia, 2006)
In the four years from 2002 to 2005, four new books on the Psalms and spirituality have been published. These are: • Stuhlmueller, C 2002. The spirituality of the Psalms. Collegeville, Minnesota: Liturgical Press. • Brueggemann, W 2002. Spirituality of the Psalms. Minneapolis: Fortress Press. • Waaijman, K 2004. Mystiek in de psalmen. Baarn: Uitgeverij Ten Have. • Firth, D G 2005. Hear , o Lord. A spirituality of the Psalms. Calver: Cliff College Publishing. In this paper, brief remarks on the context within which this publication trend takes place, are made. Each of the works is then briefly described, and general evaluative remarks are concluded with.